Development of Fourier transform infrared spectrophotometric method for identification and determination of marketed metamizole tablet preparation - NERDY NERDY; EFFENDY DE LUX PUTRA; NILSYA FEBRIKA ZEBUA; CHRISTICA ILSANNA SURBAKTI; JIHAN SAFIRA (Jurnal Natural, 2021)
Metamizole is a nonsteroidal antiinflammatory drug (NSAID) that functions as an analgesic, antipyretic, and antiinflammatory. Examination of active substance contents is a requirement that must be met to ensure the quality of drug preparations. The aims of this study were to develop and validate the Fourier Transform Infrared spectrophotometric method for the quantitation of metamizole content in marketed tablet preparation. Identification and determination of metamizole contents by Fourier Transform Infrared spectrophotometric method used methanol solvent in the wavenumber range 4000 cm–1 to 650 cm–1. The results showed that the specific wavenumbers of metamizole were 1649.3 cm–1; 1623.3 cm–1; and 1589.7 cm–1; and the contents metamizole in marketed tablet preparation ranged from (97.954 ± 0.121)% to (104.541 ± 0.257)%. From the validation method, the recovery result is 100.129%; the relative standard deviation is 0.057%; the limit of detection is 2.09526 mg/mL; the limit of quantitation is 6.34928 mg/mL; and the range 40 mg/mL to 60 mg/mL. The quantitation of metamizole contents can be carried out by Fourier Transform Infrared spectrophotometric method with accurate and precise quantitation results.